Integrated metabolomic profiling of olive oil, olive mill wastewater, and pomace from Egyptian cultivars based on UHPLC-MS/MS and NMR coupled with chemometrics - Zahran, Hamdy A.; Fayez, Shaimaa; Zayed, Ahmed; Azab, Mohamed A.; Fayek, Nesrin M.; Zhang, Lin; Capanoglu, Esra; Farag, Mohamed A. (Elsevier BV, 2026)
Olive oil and their by-products have long been regarded as valuable sources of health-promoting metabolites. Although the composition of olive oil has been widely studied, less attention has been given to olive mill wastewater (OMWW) and pomace across different cultivars (cvs.). The present study provides a comprehensive metabolic profiling of olive oil, OMWW, and pomace derived from 10 Egyptian cvs. using an integrated metabolomics strategy.A combination of 1H NMR and UHPLC-MS/MS analyses was employed, and data were interpreted using multivariate data analysis through various chemometric modelling, including unsupervised (e.g., PCA and HCA) and supervised (e.g., OPLS-DA) models. In addition, antioxidant activities were assessed in vitro using DPPH and ABTS assays, and correlations with metabolite composition were evaluated using Partial Least Squares (PLS) regression.Distinct phytochemical profiles were revealed across the different olive products. OMWW from "Chemlali black" was found to be particularly rich in phenolics and secoiridoids, while its pomace was characterized by higher levels of unsaturated fatty acids and triterpenoids (e.g., maslinic acid). NMR analyses further distinguished OMWW from pomace based on sugar and organic acid content. Moreover, metabolite-activity relationships were uncovered, with antioxidant capacity being strongly linked to metabolites such as elenolic acid derivatives, tetrahydroxy-methoxy flavanone, hydroxy-octadecadienoic acid, and citric acid. OMWW samples, especially from "Chemlali black", exhibited the most potent antioxidant activity.Valuable bioactive metabolites were identified in olive oil by-products, supporting their potential use in sustainable, health-promoting applications. "Chemlali black" and "Chemlali green" cvs. are recognized as promising sources for nutraceutical and functional product development. The use of integrated NMR and UHPLC-MS/MS platforms proved effective in differentiating olive matrices and highlighting antioxidant-related metabolic markers.
Keywords: Agricultural Science